2018
DOI: 10.1002/mpr.1727
|View full text |Cite
|
Sign up to set email alerts
|

Altered serum levels of glial cell line‐derived neurotrophic factor in male chronic schizophrenia patients with tardive dyskinesia

Abstract: Decreased GDNF levels in TD patients indicated that alterations in neurotrophic factors may be involved in the pathophysiology of TD, but the exact mechanisms need further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Another study found that serum GDNF levels in schizophrenia patients with a movement disorder called tardive dyskinesia (TD), which is thought to be due to long-term antipsychotic drug use, were lower than in normal controls and patients with schizophrenia without TD. This may indicate a neuroprotective effect of GDNF [ 18 ]. In sum, the relationship between GDNF levels and the pathogenesis of schizophrenia has not yet been sufficiently investigated, and therefore new studies are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that serum GDNF levels in schizophrenia patients with a movement disorder called tardive dyskinesia (TD), which is thought to be due to long-term antipsychotic drug use, were lower than in normal controls and patients with schizophrenia without TD. This may indicate a neuroprotective effect of GDNF [ 18 ]. In sum, the relationship between GDNF levels and the pathogenesis of schizophrenia has not yet been sufficiently investigated, and therefore new studies are needed.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study by Xiao et al reported a GDNF serum level reduction in patients with cognitive impairment ( 25 ). GDNF serum level has enormously implicated in many other neurological disorders ( 26 28 ). These are consistent with our findings which revealed a reduced GDNF serum levels in patients with PD who are constipated.…”
Section: Discussionmentioning
confidence: 99%
“…Although the data collected on the role of neurotrophines in the pathophysiology of bipolar disorder has increased, they are conflicting and far from being sufficient [12]. Moreoever, it is argued that these neurotropic factors also change in other psychiatric diseases such as major depression and schizophrenia, which implies that the change in these factors may not be unique to bipolar disorder [37,38]. In order to reveal this point, we kept cortisol level, BMI and age under control statistically in the groups and we found that GDNF and Nrn 1 levels were significantly lower while IGF-1 levels were significantly higher in bipolar manic episode patients compared to the control group.…”
Section: Discussionmentioning
confidence: 99%